IMS in Parallel Sysplex. - Jäntti, Jouko (IBM redbooks., 2003)
This IBM Redbooks publication is the first volume of a series of redbooks called IMS in the Parallel Sysplex. These redbooks describe how IMS exploits the Parallel Sysplex functions and how to plan for, implement, and operate IMS systems working together in a Parallel Sysplex. Volume 1 provides an overview of the Parallel Sysplex and the services offered to authorized programs such as IMS. It then continues with the description of the functionality that IMS provides in a Parallel Sysplex environment. Each function supported by IMS is presented in one or more chapters. The topics include: - Introduction to the Parallel Sysplex - Block level data sharing - Connectivity and workload balancing - Shared queues - Common Service Layer The other volumes in this series are: IMS in the Parallel Sysplex, Volume II: Planning the IMSplex, SG24-6928 IMS in the Parallel Sysplex, Volume III: IMSplex Implementation and Operations, SG24-6929.